The Great Theft - David L. Johnston (International Institute of Islamic Thought, 2005)
Written creeds, which always come much later than the original revelation, invariably seek to define theological “orthodoxy” over and against the perceived heresies of competing sects. Thus, in Islam, the Fiqh Akbar I stood against the Kharajites, the Wasiyat Abu Hanifah against the Qadarites and the first Mu`tazilites, and the Fiqh Akbar II against the later Mu`tazilites. Later on, such theological treatises as al-Ash`ari’s Al-Ibanah and `Abd al- Qahir al-Baghdadi’s Kitab Usul al-Din appeared. In The Great Theft, Khaled Abou El Fadl revives this tradition by stating that in the wake of numerous “acts of ugliness” committed by Muslims, the ummah has reached a grave theological crossroads. Muslims are now divided along a spectrum between two extremes. Fundamentally, this schism is one between “moderates” (the extreme being defined by those most willing to reinterpret the Islamic tradition in the light of contemporary realities) and “puritans,” who, on the basis of a selective reading of Islam’s strictest school of law (Hanbali), claim that 90 percent of human affairs are already covered by God’s law (the Shari`ah). At the heart of these diametrically opposed worldviews, he claims, is a theological decision regarding creation and the Shari`ah’s meaning. Significantly, the book’s first part is devoted to an analysis of the present crisis. In the first chapter (“Islam Torn between Extremism and Moderation”), Abou El Fadl describes the split that divides the Islamic community and helpfully defines the terms moderate (as opposed to modernist, progressive, or reformist) and puritan (not fundamentalist, militant, extremist, radical, or jihadist). From the beginning, he lays aside the common Muslim objections in the face of suicide bombings or beheadings: “the problem is with Muslims, not Islam per se.” Unfortunately, he argues, all sides claim that they are following the precepts of Islam. What is needed is a ...